Ground plan of the larval nervous system in phoronids: Evidence from larvae of viviparous phoronid. Issue 4 (4th September 2017) - Temereva, Elena N.
Abstract : Nervous system organization differs greatly in larvae and adults of many species, but has nevertheless been traditionally used for phylogenetic studies. In phoronids, the organization of the larval nervous system depends on the type of development. With the goal of understanding the ground plan of the nervous system in phoronid larvae, the development and organization of the larval nervous system were studied in a viviparous phoronid species. The ground plan of the phoronid larval nervous system includes an apical organ, a continuous nerve tract under the preoral and postoral ciliated bands, and two lateral nerves extending between the apical organ and the nerve tract. A bilobed larva with such an organization of the nervous system is suggested to be the primary larva of the taxonomic group Brachiozoa, which includes the phyla Brachiopoda and Phoronida. The ground plan of the nervous system of phoronid larvae is similar to that of the early larvae of annelids and of some deuterostomians. The protostome‐ and deuterostome‐like features, which are characteristic of many organ systems in phoronids, were probably inherited by phoronids from the last common bilaterian ancestor. The information provided here on the ground plan of the larval nervous system should be useful for future analyses of phoronid phylogeny and evolution.